Early Life Nutrition and Subsequent Education, Health, Wage, and Intergenerational Effects - Behrman, Jere R. (World Bank, Washington, DC, 2017)
This paper first summarizes recent research in developing countries that is surveyed in prominent Lancet articles and that reports, albeit based on relatively few systematic studies, substantial associations between early life nutrition and subsequent education, health, wage, and intergenerational outcomes. The rest of the paper summarizes further evidence. The next section summarizes some of the strongest micro-level evidence available based on panel data over 35 years from Guatemala on causal effects of early life nutritional improvements on adult cognitive skills and wage rates and offspring anthropometric outcomes. The subsequent section summarizes some benefit-cost analyses for early life nutritional interventions that led to such interventions being ranked highly among interventions of all types, largely on the basis of benefit-cost ratios by prominent economists in the 2004 Copenhagen Consensus. The studies reviewed in this paper indicate that improved early life nutrition in poorly nourished populations may have substantial causal effects on improving productivity and saving resources over the life cycle and into the next generation and may have benefits that substantially outweigh the costs. Thus, in addition to important direct intrinsic welfare benefits, better early life nutrition in such contexts should be a high priority in strategies for increasing growth and productivity.